Evaluation of the Effect of Acacia Nilotica Extract in Periodontitis Induced Albino Rabbit. Issue 1 (2019) - Farooq, Zahid; Zafar, Muhammad Shoaib; Khan, Muhammad Waqas A.; Bokhari, sif Ali
No abstract available